Thromboembolic events in pregnant and puerperal women after COVID‐19 lockdowns: A retrospective cohort study. Issue 1 (29th July 2021) - Gabrieli, Dana; Cahen‐Peretz, Adva; Shimonovitz, Tzvika; Marks‐Garber, Keren; Amsalem, Hagai; Kalish, Yosef; Lavy, Yuval; Walfisch, Asnat
Abstract: Objective: To explore the indirect impact of the COVID‐19 pandemic on patterns of pregnancy‐related venous thromboembolism (VTE) events, mediated by population mobility restrictions during lockdown periods. Methods: Pregnancy‐related VTE hospitalizations were identified through a code‐targeted search of the Hadassah Medical Center's computerized database. A manual analysis of relevant medical records was performed, and cases diagnosed throughout the year 2020 were compared to those diagnosed during 2019 and 2018. Statistical analyses studied obstetrical outcomes, as well as the extent and treatment of VTE events during the COVID‐19 pandemic compared to those of preceding years, stratified by pre‐, intra‐, and post‐lockdown periods. Results: The incidence of pregnancy‐related thromboembolic events during 2020 was 0.16% of all deliveries, significantly higher than in 2018 and 2019 (0.06% and 0.1%, respectively; P  < 0.05). Higher rates of VTE events were found during post‐lockdown periods in 2020, compared with corresponding time periods in 2019 and 2018. Conclusion: The present data suggest that lockdown periods impact pregnancy‐related VTE hospitalizations, possibly as a result of restricted population mobility. Increased awareness of this undesirable outcome may aid health policymakers in the continuing struggle with epidemics. Synopsis: The present study suggests an association between national lockdowns resulting in relative immobilization and an increase in the incidence of pregnancy‐related venous thromboembolism events.